The Effect of Antivascular Endothelial Growth Factor on the Development of Adhesion Formation in Laparotomized Rats: Experimental Study - Basbug, Murat; Bulbuller, Nurullah; Camci, Cemalettin; Ayten, Refik; Aygen, Erhan; Ozercan, Ibrahim Hanifi; Akbulut, Sami (Hindawi Ltd, 2011)
Aims. This study determined the effects of a single dose of bevacizumab, an antiangiogenic recombinant monoclonal antibody that specifically targets vascular endothelial growth factor (VEGF), on adhesion formation in the rat cecal abrasion model. Methodology. Thirty female Wistar albino rats (200-224 g) were divided into three groups. All rats underwent laparotomy at which time cecal wall abrasion and abdominal wall injuries were induced. Group I (control) underwent only the abrasion procedure; Groups II and III received saline or bevacizumab intraperitoneally, respectively, following the abrasion. The rats were killed on postoperative day 7, and the severity of adhesions was evaluated, together with histopathological fibrosis parameters and immunohistochemical staining to identify the VEGF receptor. Results. The mean adhesion severity score in Groups I-III was 2.5 +/- 0.52, 2.4 +/- 0.69, and 0.7 +/- 0.82, respectively; the score in Group III was significantly lower than that in Groups I (P < 0.001) and II (P < 0.001). In the histopathological evaluation, the mean fibrosis score in Group III was significantly lower that the scores in Groups I (P < 0.001) and II (P < 0.001). VEGF staining of the adhesion areas in Group III was significantly lower than that in Groups I (P < 0.001) and II (P < 0.001). Conclusion. Bevacizumab decreases adhesion formation following laparotomy in rats by blocking VEGF receptor occupancy.
Keywords: Postoperative Peritoneal Adhesions; Plasminogen-Activator; Bevacizumab; Prevention; Vegf; Antibody; Pathogenesis; Expression; Efficacy